URGENSI KEBUTUHAN PEMBELAJARAN EKONOMI BERKARAKTER BERBASIS KELAS DI SMA - Endang Purwaningsih (Jurnal Visi Ilmu Pendidikan, 2022)
AbstractThis study aims to identify the need for developing class-based character-based economic teaching materials for high school students. This research is a qualitative research with a case study research type. The research location is located in the city of Singkawang, with research informants involving 8 economics teachers at the high school level, with data collection techniques in the form of focus group discussions. The data analysis of this research uses three activity lines that occur simultaneously, namely: data reduction, data presentation, and conclusion drawing. The results of the study found that: (1) to date, there is no class-based character economy teaching material for high school students in the city of Singkawang; (2) It is necessary to develop class-based character-based economic teaching materials for high school students in the city of Singkawang. Keywords: Economic learning, class-based, character